Economic Evidence Regarding Alcohol Price Elasticities and Price Responses by Heavy Drinkers, Binge Drinkers, and Alcohol-Related Harms: Summary of Results for Meta-Analysis, Systematic Reviews, and Natural Experiments in Alcohol Policy - Jon P. Nelson (Public Health, 2025)
Numerous economic studies examine effects of alcohol price and tax changes on drinking,drinking patterns and alcohol-related harms. The consensus view is that prices are an effective instrument for addressing issues of heavy drinking, binge drinking, and adverse outcomes associated with alcohol. In a series of published studies, I present evidence that this view is overly optimistic, and results for alcohol prices are more varied, complex, or nuanced. This paper provides a brief overview of main results in eight studies. Alcohol tax and price interventions have selective, rather than broad, impacts on sub-populations, drinking patterns, and alcohol-related harms.